Akibat Hukum Materi Muatan Peraturan Negeri yang Tidak Sesuai dengan Judul Peraturan Negeri - Salasiwa, Niklas; Pietersz, Jemmy Jefry; Matitaputty, Merlien Irene (CAPITAN: Constitutional Law & Administrative Law Review, 2023)
Ambon City Regional Regulation number 10 of 2017 concerning the Appointment, Election, Inauguration and Dismissal of the Head of State Government is the legal basis for every implementation of state regulations in Ambon City, this means that every state regulation made must be based on Ambon City Regulation Number 10 of 2017 2017. In making regulations, whether regional regulations or state regulations, appropriate and appropriate adjustments are needed in terms of determining the title and material content contained in the regulation, but it is not uncommon for there to be regulations that are not appropriate. The mismatch between the title of a state regulation and the content of the content material is certainly something that is very contrary to the law which will of course give rise to legal consequences. One of the state regulations which has a different title and content material is the Hative Kecil state regulation Number 6 of 2020 concerning the determination of house points. parents in the Hative Kecil country, with the title determining the terms of the parental home, the content material contained in this state regulation should only be limited to the scope of the parental home in the Small Hative State, but unfortunately the content material contained in the state regulations already covers all matters regarding Small Hative Country, starting from the appointment of the head of government of Small Hative Country, the election of the head of the state government, to the dismissal of the head of the state government, of course it is clear that the title of this state regulation does not match the existing content material, for this reason, this difference is certainly contrary to law and can give rise to legal consequences.